Efek Pertanyaan Pengarah Dalam Pembelajaran Sains Terhadap Penguasaan Konsep Pada Siswa SLTP - Taufik Rahman (EDUCARE, 2002)
Questioning plays an important role in science teaching learning process. The effect of prompting question in science (biology) teaching learning process on increasing student’s understanding  was evaluated in this study.  The method used in the study was experimental involving students in experimental group who used student experiment worksheet with prompting question and students in control group who used experiment  worksheet without prompting question. The study was carried out in the sight organ of Invertebrate in Junior High School. To evaluate the different effect of prompting question and without prompting question on increasing student’s understanding, pretest  and postes  was  given to the two group. The study revealed that the use of prompting question more efectively increased student’s understanding to the concept than the use of without prompting question.Keywords: experiment student worksheet,  prompting question